Computer based speech prosody teaching system. (July 2018) - Sztahó, Dávid; Kiss, Gábor; Vicsi, Klára
Highlights: A novel prosody teaching system for children is proposed. Visual and automatic feedback was applied optimized for children. Evaluation of automatic assessment was done with experts. The software resulted improved pronunciation in the case of test subjects. Abstract: Children who are born with a profound hearing loss have no or only distorted acoustic speech target to imitate and compare their own production with. Computer based visual feedback, visual presentation of speech on screen has shown to be an effective supplement of incomplete or distorted auditory feedback in the case of children with grave hearing-impairment. In this paper, we introduce a novel prosody teaching system where intensity (accent), intonation and rhythm are presented visually for the students (in both separate and combined display mode) as visual feedback and automatic assessment scores are given jointly and separately for the goodness of intonation and rhythm. Evaluation of the automatic assessment was done with cooperation of experts in the field of treatment of hard of hearing children. The results showed that the automatic assessment scores correspond to the subjective evaluations given by the teachers. The evaluation of the whole system was done in a school for hard of hearing children, by comparing the development of a group of students using our prosody teaching system with the development of a control group. The speaking ability of students were compared by a subjective listening experiment after a 3 months teaching course. The students who used the computer based prosody teaching software could produce nicer prosody than the students in the control group.